Cybercrime in Islamic Perspective: The Role of Islamic Education & Criminal Law in Combating Online Sexual Crimes - Fatin Hamamah (Permata : Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the phenomenon of cybercrime, especially online sexual crimes (cybersex), from an Islamic perspective and the role of Islamic education and criminal law in overcoming it. Online sexual crimes are increasingly growing along with the rapid progress of information and communication technology, which raises new challenges in the fields of law and morality. In this context, Islamic education and the criminal law system have an important role in preventing and eradicating such acts.This study uses a qualitative method with a descriptive analytical approach, collecting data from Islamic law sources and criminal law studies related to cybercrime at SMP Islam Plered Cirebon. The results of the study indicate that Islamic education can provide a strong moral foundation in preventing the misuse of technology, while Islamic and state criminal law offer strict sanctions for perpetrators of cybersex. The implementation of both in society is expected to create better awareness and self-control among individuals. The social implications of this study show the importance of integration between religious education and law in building a society that is aware of the negative impacts of technology. The role of families, educational institutions, and the government in providing education about the dangers of cybersex as well as strict law enforcement is needed to create a safe and responsible cyberspace. The results of this study have implications for the need to strengthen Islamic education and curriculum on digital ethics, reform the legal system, develop comprehensive prevention programs involving the role of parents, and increase digital legal literacy in society to deal with cybersex problems effectively. Keywords: Cybercrime; Islamic Education; Criminal Law; Online Sexual Crimes; Prevention